Mewujudkan Transisi yang Lancar: Strategi Menarik dalam Mendukung Anak Menuju SD dari PAUD - indah Pebriani; Kinda Handayani (Journal of Information Systems and Management (JISMA), 2024)
This research aims to eliminate the calistung test from the process of admitting new students to elementary school. Implement an introductory period for new students during the first two weeks (in PAUD and SD). Implementing learning that builds six foundational abilities of children (in PAUD and SD). The Fun Transition Movement from PAUD to SD is a joint movement that underlies the transition of PAUD students to SD/MI/equivalent in a fun way and starts from the new school year. In this study report, a descriptive qualitative method was used by taking notes because the data source was obtained by listening to the oral narrative from the KEMDIKBUD RI YouTube channel entitled "Merdeka Belajar episode 24: The fun transition from PAUD to SD" which was explained directly by the Minister of Education, Indonesian culture, research and technology, Mr. Nadiem Anwar Makariem. This research is based on the misconception of learning practices in Early Childhood and Elementary School Education, that building abilities in children needs to be done gradually and in a fun way so that the good benefits of learning are achieved.